Nuclear Charge Radii of the Nickel Isotopes Ni-58-68,Ni-70 - Malbrunot-Ettenauer, S.; Kaufmann, S.; Bacca, S.; Barbieri, C.; Billowes, J.; Bissell, M. L.; Blaum, K.; Cheal, B.; Duguet, T.; Ruiz, R. F. Garcia; Gins, W.; Gorges, C.; et al. (Physical Review Letters, 2022)
Collinear laser spectroscopy is performed on the nickel isotopes Ni-58-68,Ni-70, using a time-resolved photon counting system. From the measured isotope shifts, nuclear charge radii R-c are extracted and compared to theoretical results. Three ab initio approaches all employ, among others, the chiral interaction NNLOsat, which allows an assessment of their accuracy. We find agreement with experiment in differential radii delta < r(c)(2)> for all employed ab initio methods and interactions, while the absolute radii are consistent with data only for NNLOsat. Within nuclear density functional theory, the Skyrme functional SV-min matches experiment more closely than the Fayans functional Fy(Delta r, HFB).
CRIS-Team WoS Importer:2022-02-04